PENGARUH PEMAHAMAN KEBIJAKAN PERPAJAKAN TERHADAP NIAT UNTUK PATUH DENGAN KESADARAN PERPAJAKAN SEBAGAI MEDIASI - Ouduil, Edwardo Chlopas; Susanti, Mila; Ismail, Marthinus (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
In order to increase state revenue through taxes, the government has developed various strategies aimed at increasing the compliance of taxpayers (WP). One of the strategies carried out was through the issuance of tax policies which were expected to be able to raise the awareness of taxpayers and finally cause the intention to comply with all tax regulations. Therefore, the study aimed to seek certainty about the intention to comply from taxpayers from the existence of tax policies rolled out by the government with taxpayer awareness as a lever variable. This study used primary data by sharing questionnaires virtually. The sample data was collected using the purposive sampling method, to obtain perceptions from respondents, especially those who already know tax policies. The data were analyzed using descriptive statistics and statistical regression. The results of the study found that the intention to comply began with an understanding of tax policies and the awareness of taxpayers. The intention to comply directly comes from the understanding of tax policy, but some taxpayers stated that it was catalyzed because of tax awareness from taxpayers.